Examining the predictors influencing emotional exhaustion among food and beverages staff at 4-and 5-star hotels in Selangor - Abdul Hadi, Arnieyantie; Hashim, Nurul Huda; Ngelambong, Anderson; Muhamad Zulkeri, Nurr Nisrina Falihah; Mohd Hamidan, Nur Khairunnisaa’ Afifah (GADING Journal for the Social Sciences, 2024)
Employees at upscale hotels in the hospitality sector are expected to provide exceptional service, which frequently results in a great deal of stress. Therefore, this study aims to investigate the factors that influence emotional exhaustion among food and beverage (F&B) staff at 4- and 5-star hotels in Klang Valley. Specifically, factors including work overload and demographic profiles like gender, age, marital status, work experience, and job position were considered. The study utilised a quantitative methodology through a survey via an online poll, which was answered by 110 F&B staff members of 4- and 5-star hotels. The responses were analysed using the Statistical Package for the Social Sciences (SPSS) version 28. Descriptive and correlation analysis were used to assess the presented hypotheses. The findings showed that among F&B hotel employees, work overload and demographic characteristics (age, marital status, work experience, and job position) had a substantial impact on emotional exhaustion. The regression analysis results demonstrated that, in comparison to gender, factors like age, marital status, work experience, work overload, and job position within the F&B department had a more substantial impact on the emotional exhaustion that F&B hotel employees experienced. The findings of this study may help managers and HR specialists forecast when work burnout will start and what factors lead to the early identification of burnout.